Angola : First Review of the Extended Arrangement Under the Extended Fund Facility, Requests for a Waiver of Nonobservance of a Performance Criterion, and Modifications of Performance Criteria, and Financing Assurances Review-Press Release; Staff Report; and Statement by the Executive Director for Angola. (IMF Staff Country Reports; Country Report, 2019)
A 36-month Extended Arrangement under the Extended Fund Facility (hereafter the 'arrangement') was approved last December, with access of SDR 2,673 million (361 percent of quota). Lower international oil prices would reduce oil revenues, widen the current account deficit, and stymie growth recovery. The authorities are implementing a proper policy response to the weakened outlook, through a conservative supplementary budget for 2019, alternative sources of cheaper financing, and progress toward a more flexible exchange rate regime.